Diagnosis and staging of hepatocellular carcinoma (HCC): current guidelines. Issue 101 (April 2018) - Ayuso, Carmen; Rimola, Jordi; Vilana, Ramón; Burrel, Marta; Darnell, Anna; García-Criado, Ángeles; Bianchi, Luis; Belmonte, Ernest; Caparroz, Carla; Barrufet, Marta; Bruix, Jordi; Brú, Concepción
Highlights: Surveillance based on biannual ultrasonography allows early detection of Hepatocellular Carcinoma (HCC) in patients at risk. Only patients at risk that could be treated if diagnosed of HCC should be included in surveillance programs. Diagnosis of HCC in early stages is key to apply effective therapy and expand life expectancy. Typical vascular profile of HCC on imaging allows non-invasive diagnosis of HCC in patients at risk with sensitivity and specificity rates of 60% and 96–100% respectively. The added benefit of new diagnostic tools for HCC based on MRI and PET in the decision making process is pending on robust data on specificity rates. Treatment should be indicated only when the diagnosis of HCC is secure to avoid overtreatment of suspicious lesions. Abstract: One of the key strategies to improve the prognosis of HCC, beside prevention, is to diagnose the tumor in early stages, when the patient is asymptomatic and the liver function is preserved, because in this clinical situation effective therapies with survival benefit can be applied. Imaging techniques are a key tool in the surveillance and diagnosis of HCC. Screening should be based in US every 6 months and non-invasive diagnostic criteria of HCC based on imaging findings on dynamic-MR and/or dynamic-CT have been validated and thus, accepted in clinical guidelines. The typical vascular pattern depicted by HCC on CT and or MRI consists on arterial enhancement, stronger than the surrounding liver (wash-in), and hypodensity or hyposignal intensity compared to the surrounding liver (wash-out) in the venous phase. This has a sensitivity of around 60% with a 96–100% specificity. Major improvements on liver imaging have been introduced in the latest years, adding functional information that can be quantified: the use of hepatobiliary contrast media for liver MRI, the inclusion of diffusion-weighted sequences in the standard protocols for liver MRI studies and new radiotracers for positron-emission tomography (PET). However, all them are still a matter of research prior to be incorporated in evidence based clinical decision making. This review summarizes the current knowledge about imaging techniques for the early diagnosis and staging of HCC, and it discusses the most relevant open questions.